Tetramethylpyrazine alleviates cerebral ischemia-reperfusion injury via NRF2/HO-1/GPX4-mediated ferroptosis inhibition - Hengpei Gong; Yinjun Lu; Lingfeng Wang; Xueyuan Gong; Jingfang Zhao; Zhenxin Li (Tissue and Cell, 2027)

Time-of-day-dependent effects of exercise on the hepatic clock and proteome in high-fat diet-fed mice - Chunxiu Huang; Xiaodan Wang; Huanghao Zhou; JingFang Zhu; Yue Hu; Huijuan Wu; Xinru Yu; Cong Chen (Journal of Physiology and Biochemistry, 2026)

Radio frequency pasteurization of spices under stationary, moving, and mixing conditions: Linking temperature distribution with microbial inactivation, and moisture uniformity - Yingwen Tang; Shangjiayi Bai; Jincheng Ma; Jingfang Ao; Shaojin Wang; Long Chen (Food Control, 2026)

N-doped hollow carbon nanocage-CNT confined FeNi nanoreactors for PMS activation toward sulfadiazine degradation - Junchang Wang; Yulai He; Jingfang Hu; Limin Chen; Ye Hong; Wenjin Chen (Journal of Water Process Engineering, 2026)

Millennial cold–dry events during marine isotope stage 11a based on sedimentary records from the Heqing Basin and their global climatic dynamical responses - Guohui Liu; Xinwen Xu; Shenghui Wang; Lirong Hou; Yuqing Zhang; Liu Yang; Jingfang Zhang; Yuzhu Zhang; Hui Zhao; Chaofeng Fu; Xiaoke Qiang; Wen Liu; et al. (Global and Planetary Change, 2026)

Maturity-driven changes in radio frequency-vacuum drying of kiwifruit: Mechanistic insights from dielectric properties and microstructure evolution - Jingfang Ao; Haihui Zhu; Tingting Xu; Shaojin Wang; Chung Lim Law; Long Chen (Food Research International, 2026)

Tailored electronic structure of copper species in spatially controlled Cu-SSZ-13 for efficient denitration - Pengkai Jin; Wang Song; Qianni Cheng; Wanting Yan; Gehui Wang; Jingfang Sun; Changjin Tang; Lin Dong (Chemical Engineering Journal, 2026)

pH-responsive, self-lubricating hyaluronic acid-chondroitin sulfate-chitosan hydrogel for articular cartilage repair - Haofeng Qiu; Jingfang Zheng; Zheyu Yao; Ximing Cai; Gaoke Pan; Xufeng Mao; Xin Zhao; Lei Shao; Dangsheng Xiong; Rong Wang; Yi Zhang (Carbohydrate Polymers, 2026)

Integrated metabolomics and transcriptomics analyses to explore the potential coloration mechanism in different colored T. sinensis cultivars - Xiao Wang; Zihui Wang; Jinze Feng; Beibei Zhang; Jingfang Zhang; Cheng Wang (Food Bioscience, 2026)

Holistic evolution of the Bohai Sea complex system: Insights from interacting drivers - Han Huang; Tao Zou; Teng Liu; Hongyu Wang; Zhixuan Wang; Ningning Tao; Yanfang Li; Hao Fan; Fei Xie; Weidong Zhai; Guizhi Wang; Yongwen Zhang; et al. (Marine Environmental Research, 2026)

RECA: an efficient deep learning model for the rapid identification of cotton leaf diseases - Jingfang Wang; Hongyun Song; Madineh Bijani; Longguo Wu; Laixiang Xu (Plant Biotechnology Reports, 2026)

Establishment of detection method of chicken infectious anemia virus based on CRISPR/Cas12a system - Chenchen Sheng; Jingfang Wang; Mengyuan Tan; jingwen Zhang; Mengran Sun; Jiumeng Sun; Ying Shao; Jian Tu; Liangqiang Zhu; Xiangjun Song (Research in Veterinary Science, 2026)

Cross-scale long-term spatiotemporal dynamics and influencing indicators of summer urban heat risk in mega-urban agglomeration - Jiachen Liu; Xiaofang Wang; Jingfang Yan; Xinfei Zhao; Wenke Chen; Le Yin; Baolei Zhang (Journal of Cleaner Production, 2025)

An integrated mechanistic modeling and machine learning for radio frequency heating uniformity optimization of canola seeds - Jilong Gao; Yu Liu; Jingfang Ao; Shaojin Wang; Jiajia Chen; Long Chen (Innovative Food Science & Emerging Technologies, 2025)

Complex network approaches for identifying global drought teleconnection patterns - Wenliang Wang; Lei Zhou; Congcong He; Yongwen Zhang; Zhiqiang Gong; Na Ying; Panjie Qiao; Jianjun Wu; Hongquan Sun; Jingfang Fan (Global and Planetary Change, 2025)

Multidimensional quality assessment (nutrients and aroma) of dried kiwifruit: Unveiling the advantages of radio frequency-vacuum drying - Jingfang Ao; Shaojin Wang; Xingshu Li; Chung Lim Law; Long Chen (Food Chemistry, 2025)

Dendritic-honeycomb porous polyoxometalate/MXene films for supercapacitor applications - Xinzheng Li; Yingyi Ma; Xinran Li; Yu Si; Kexin Liu; Shiyun Wang; Zhihao Zhu; Jingfang Li (Chemical Engineering Journal, 2025)

The individual and combined effects of coastline changes and riverine input on water quality: A multi-scenario simulation perspective - Jingfang Lu; Wei Zheng; Dehai Song; Xianqing Lv; Weimin Wang; Honghua Shi (Marine Pollution Bulletin, 2025)

Effects of stir-frying frequency on meat quality via multimodal infrared & accelerometer platform - Yibing Yuan; Liangyu Xue; Xiaojia Hu; Guowei Gao; Wenzheng Zhu; Yangjun Wang; Jingfang Hu; Huixin Tian; Chunhui Zhang; Wensong Wei (International Journal of Gastronomy and Food Science, 2025)

Carbon-confinement modulated interfacial water structure for accelerated dissociation kinetics towards hydrogen evolution - Fanpeng Cheng; Yue Yu; Yulu Wan; Dashuai Wang; Shangqing Chen; Jingfang Zhang; Huijuan Guo; Yang Xia; Yi Huang; Lijuan Shi; Liwei Cheng; Qun Yi (Chemical Engineering Journal, 2025)

Linear-light regulated bidirectional electron transfer of a pyromellitic diimide-based photochromic coordination polymer for inkless and erasable printing and information anticounterfeiting - Jingfang Wang; Pengfei Hao; Shimin Zhang; Yi Xu; Jin Qin; Junju Shen; Yunlong Fu (Chemical Engineering Journal, 2025)

Prevalence of Avian Influenza Viruses and Biomolecular Analysis of H9N2 Subtype in Live Poultry Markets from 2021 to 2023 in Changsha, China - Xian Zhang; Yutong Wang; Xiaoyu Li; Zheng Huang; Huiyuan Fu; Ruiqing Pei; Caiying Zhu; Yu Di; Shan Chen; Jingfang Chen; Mingzhong Xu; Xuewen Yang; et al. (Food and Environmental Virology, 2025)

Mitofusin 2 Mediates the Protective Effect of NR6A1 Silencing Against Neuronal Injury in Experimental Stroke Models - Bingtian Xu; Zhuhe Liu; Kechun Chen; Qian Zhao; Haixia Wen; Jingfang Lin; Jiangping Xu; Haitao Wang; Honghao Wang; Yuanyuan Wang (Molecular Neurobiology, 2025)

Raw meat 3D laser scanning imaging: Optimized by adaptive contour unit - Lingping Bu; Huixin Tian; Zhen Qiao; Xiaojia Hu; Guowei Gao; Bo Qi; Zhize Wang; Jingfang Hu; Chunhui Zhang; Dequan Zhang; Wensong Wei (Food and Bioproducts Processing, 2025)

Protective effect of astragaloside IV against zinc oxide nanoparticles induced human neuroblastoma SH-SY5Y cell death: a focus on mitochondrial quality control - Liwei Wang; Lu Zhang; Yang Yun; Tingting Liang; Chaoqun Yan; Zhuoya Mao; Jingfang Zhang; Baoshe Liu; Jian Zhang; Taigang Liang (Molecular and Cellular Biochemistry, 2025)

Comprehensive study of heavy precipitation events over land using climate network analysis - Kaiwen Li; Ming Wang; Kai Liu; Jingfang Fan (Journal of Hydrology, 2025)

A global optimization method based on fuzzy clustering Kriging for aerobic wastewater treatment - Yaohui Li; Shuting Wang; Yizhong Wu; Zebin Zhang; Jingfang Shen (Journal of Environmental Management, 2025)

Dynamic characterization of volatile and non-volatile profiles during Toona sinensis microgreens growth in combination with chemometrics - Beibei Zhang; Yunhui Zhai; Zichao Wu; Cheng Wang; Jingfang Zhang (Food Research International, 2025)

Synchronization patterns of extreme rainfall events in Southwest China - Panjie Qiao; Xiaojuan Wang; Wenqi Liu; Shuai Li; Yongwen Zhang; Guolin Feng; Jingfang Fan (Climatic Change, 2025)

Improved Deadbeat Predictive Direct Power Control for Three-Phase PWM Rectifier Based on LADRC - He Ma; Xuliang Yao; Jingfang Wang; Xinghong Luo; Shengqi Huang (Journal of Marine Science and Engineering, 2025)
In modern marine vessels equipped with electric propulsion systems, rectifiers are commonly used as part of the setup. However, the conventional deadbeat predictive direct power control strategy for three-phase voltage source pulse-width modulation (PWM) rectifiers tends to underperform when subjected to load variations and external disturbances. To address these limitations, this paper proposes an enhanced linear active disturbance rejection control (LADRC), incorporating virtual capacitance and an improved equivalent input disturbance strategy. The integration of virtual capacitance in the LADRC is specifically applied during load transitions. Virtual capacitance is a capacitor element simulated through the control strategy. It enhances voltage stability and dynamic response capability by compensating for voltage fluctuations and power deficits in the system. By providing a virtual active power, this approach substantially improves power tracking performance, reducing the DC voltage drop and settling time by 60% and 74%, respectively. In addition, the proposed strategy is easy to implement and does not add complexity to the LADRC. Moreover, the equivalent input disturbance is refined through virtual capacitance, enabling accurate disturbance estimation. As a result, the active power ripple and current total harmonic distortion under disturbances are reduced by 44% and 40%, respectively. The stability of the proposed strategy is comprehensively analyzed, and experimental results from a prototype system validate its effectiveness and accuracy.

Adding non-crop plants enhances parasitoid fitness on potato plants, but not pest densities - Yusha Wang; Yongping Zhou; Ruwen Li; Ambreen Masqsood; Hongsong Chen; Zhenqiang Qin; Jingfang Yang; Jiali Zhang; Lin Jing; Huihua Tan; Zhongshi Zhou (Crop Protection, 2025)

Systematic engineering for high-level production of β-nicotinamide mononucleotide from NAM and ribose - Tianqi Bao; Pingping Weng; Jingfang Wang; Shumei Cui; Yong Tao; Jianzhong Huang; Xinwei Yang; Chongrong Ke (Food Bioscience, 2025)

Interface engineering of Platinum–Copper alloy/titanium dioxide for enhanced photocatalytic carbon dioxide reduction - Xin Wang; Wei Tan; Bo Peng; Shangcong Sun; Xue Li; Kaiqiang Wang; Jiawei Ji; Haohong Liao; Jingfang Sun; Qing Tong; Haiqin Wan; Lin Dong (Environmental Research, 2024)

Double template synthesis of N/S co-doped shrimp shell derived biochar for efficient sulfadiazine degradation: The role of non-radical pathway - Yulai He; Jiaqi Wang; Lele Lei; Yushi Ai; Hongmei He; Jin Huang; Limin Chen; Jingfang Hu; Wenjin Chen (Journal of Environmental Chemical Engineering, 2024)

Electron beam and X-ray irradiation promote extraction of bioactive compounds from walnut green husk: Structural, physicochemical, and functional properties - Ruolin Wang; Heyu Shen; Junqing Bai; Guangming Zou; Yubing Shi; Jingfang Ao; Heting Qi; Yingying Cai; Anwei Luo (Food Bioscience, 2024)

High Frequency of Autoantibodies in COVID-19 Patients with Central Nervous System Complications: a Multicenter Observational Study - Jingfang Lin; Dong Zheng; Decai Tian; Pei Zheng; Hongya Zhang; Chuo Li; Chunliang Lei; Fudong Shi; Honghao Wang (Molecular Neurobiology, 2024)

Co-occurrence patterns of gut microbiome, antibiotic resistome and the perturbation of dietary uptake in captive giant pandas - Yuhao Fu; Feiran Jia; Jingfang Su; Xinyao Xu; Yuqin Zhang; Xiangzhen Li; Xin Jiang; Andreas Schäffer; Marko Virta; James M. Tiedje; Fang Wang (Journal of Hazardous Materials, 2024)

CeO2 nanocages with tetra-enzyme mimetic activities for dual-channel ratiometric colorimetric detection of microcystins-LR - Guodong Wang; Jingfang Guo; Jing Zou; Zhen Lei (Analytica Chimica Acta, 2024)

Integration of transcriptome, volatile and non-volatile metabolite profile reveals characteristic aroma formation in Toona sinensis - Beibei Zhang; Lifang Hao; Jing Zhang; Jinze Feng; Cheng Wang; Jingfang Zhang (Food Chemistry, 2024)

Quaternary pollen record and paleoenvironmental evolution of the Bohai Sea strait - Jingfang Lu; Wei Huang; Jun Sun; Feifei Wang; Yuexin Gao; Xin Fan; Daolai Zhang (Regional Studies in Marine Science, 2023)

Genome-wide association mapping combined with gene-based haplotype analysis identify a novel gene for shoot length in rice (Oryza sativa L.) - Tifeng Yang; Jingfang Dong; Junliang Zhao; Longting Zhang; Lian Zhou; Wu Yang; Yamei Ma; Jian Wang; Hua Fu; Jiansong Chen; Wenhui Li; Haifei Hu; et al. (Theoretical and Applied Genetics, 2023)
Key message Genome-wide association mapping revealed a novel QTL for shoot length across multiple environments. Its causal gene, LOC_Os01g68500 , was identified firstly through gene-based haplotype analysis, gene expression and knockout transgenic verification. Abstract Strong seedling vigor is an important breeding target for rice varieties used in direct seeding. Shoot length (SL) is one of the important traits associated with seedling vigor characterized by rapid growth of seedling, which enhance seedling emergence. Therefore, mining genes for SL and conducting molecular breeding help to develop varieties for direct seeding. However, few QTLs for SL have been fine mapped or cloned so far. In this study, a genome-wide association study of SL was performed in a diverse rice collection consisting of 391 accessions in two years, using phenotypes generated by different cultivation methods according to the production practice, and a total of twenty-four QTLs for SL were identified. Among them, the novel QTL qSL-1f on chromosome 1 could be stably detected across all three cultivation methods in the whole population and indica subpopulation. Through gene-based haplotype analysis of the annotated genes within the putative region of qSL-1f , and validated by gene expression and knockout transgenic experiments, LOC_Os01g68500 (i.e., Os01g0913100 in RAP-DB) was identified as the causal gene for SL, which has a single-base variation (C-to-A transversion) in its CDS region, resulting in the significant difference in SL of rice. LOC_Os01g68500 encodes a DUF538 (Domain of unknown function) containing protein, and the function of DUF538 protein gene on rice seedling growth is firstly reported in this study. These results provide a new clue for exploring the molecular mechanism regulating SL, and promising gene source for the molecular breeding in rice.

A pervasive phosphorylation cascade modulation of plant transcription factors in response to abiotic stress - Wang Baoxiang; Sun Zhiguang; Liu Yan; Xu Bo; Li Jingfang; Chi Ming; Xing Yungao; Yang Bo; Li Jian; Liu Jinbo; Chen Tingmu; Fang Zhaowei; et al. (Planta, 2023)

Effects of nitrogen and phosphorus supply levels and ratios on soil microbial diversity-ecosystem multifunctionality relationships in a coastal nontidal wetland - Kai Sun; Jingfang Cai; Xiaoling Liu; Lijuan Yang; Hongli Li; Guangmei Wang; Xingliang Xu; Feihai Yu (Science of The Total Environment, 2023)

Integrated volatilomic profiles and chemometrics provide new insights into the spatial distribution and aroma differences of volatile compounds in seven Toona sinensis cultivars - Cheng Wang; Chendan Fu; Yanfang Li; Yilan Zhang; Beibei Zhang; Jingfang Zhang (Food Chemistry, 2023)

Integrated transcriptomic and volatilomic profiles to explore the potential mechanism of aroma formation in Toona sinensis - Cheng Wang; Beibei Zhang; Yanfang Li; Jing Hou; Chendan Fu; Zihui Wang; Jingfang Zhang (Food Research International, 2023)

Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY - Zhe Wang; Xu Duan; Guangyue Ren; Jingfang Guo; Jiangtao Ji; Yiming Xu; Weiwei Cao; Linlin Li; Mengyue Zhao; Yuan Ang; Xin Jin; Bhesh Bhandari; et al. (Food Chemistry, 2023)

The inhibitory mechanism of pentacyclic triterpenoid acids on pancreatic lipase and cholesterol esterase - Heyu Shen; Jun Wang; Jingfang Ao; Lixia Ye; Yubing Shi; Yujie Liu; Mengyang Li; Anwei Luo (Food Bioscience, 2023)

The neglected potential source of microplastics from daily necessities: A study on protective mobile phone cases - Qilu Li; Meng Yuan; Yuan Chen; Xinjie Jin; Jingfang Shangguan; Jinle Cui; Shixiang Chang; Mengran Guo; Yan Wang (Journal of Hazardous Materials, 2023)

The impact of three related emission industries on regional atmospheric chlorinated paraffins pollution - Qilu Li; Shanshan Jiang; Yajing Li; Jingjing Su; Jingfang Shangguan; Mengdi Zhan; Yan Wang; Xianfa Su; Jun Li; Gan Zhang (Environmental Pollution, 2023)

Increased greenhouse gas emissions intensity of major croplands in China: Implications for food security and climate change mitigation - Jingting Zhang; Hanqin Tian; Hao Shi; Jingfang Zhang; Xiaoke Wang; Shufen Pan; Jia Yang (Global Change Biology, 2020)
Balancing crop production and greenhouse gas (GHG) emissions from agriculture soil requires a better understanding and quantification of crop GHG emissions intensity, a measure of GHG emissions per unit crop production. Here we conduct a state‐of‐the‐art estimate of the spatial‐temporal variability of GHG emissions intensities for wheat, maize, and rice in China from 1949 to 2012 using an improved agricultural ecosystem model (Dynamic Land Ecosystem Model‐Agriculture Version 2.0) and meta‐analysis covering 172 field‐GHG emissions experiments. The results show that the GHG emissions intensities of these croplands from 1949 to 2012, on average, were 0.10–1.31 kg CO 2 ‐eq/kg, with a significant increase rate of 1.84–3.58 × 10 –3 kg CO 2 ‐eq kg −1 year −1 . Nitrogen fertilizer was the dominant factor contributing to the increase in GHG emissions intensity in northern China and increased its impact in southern China in the 2000s. Increasing GHG emissions intensity implies that excessive fertilizer failed to markedly stimulate crop yield increase in China but still exacerbated soil GHG emissions. This study found that overfertilization of more than 60% was mainly located in the winter wheat–summer maize rotation systems in the North China Plain, the winter wheat–rice rotation systems in the middle and lower reaches of the Yangtze River and southwest China, and most of the double rice systems in the South. Our simulations suggest that roughly a one‐third reduction in the current N fertilizer application level over these “overfertilization” regions would not significantly influence crop yield but decrease soil GHG emissions by 29.60%–32.50% and GHG emissions intensity by 0.13–0.25 kg CO 2 ‐eq/kg. This reduction is about 29% and 5% of total agricultural soil GHG emissions in China and the world, respectively. This study suggests that improving nitrogen use efficiency would be an effective strategy to mitigate GHG emissions and sustain China's food security.

Evolution of the novel coronavirus from the ongoing Wuhan outbreak and modeling of its spike protein for risk of human transmission - Xintian Xu; Ping Chen; Jingfang Wang; Jiannan Feng; Hui Zhou; Xuan Li; Wu Zhong; Pei Hao (Science China Life Sciences, 2020)

Effects of Soil Properties and Land Use Types on the Bioaccessibility of Cd, Pb, Cr, and Cu in Dongguan City, China - Haoqi Tian; Yuzhe Wang; Jingfang Xie; Hua Li; Yuen Zhu (Bulletin of Environmental Contamination and Toxicology, 2020)

Hybrids of oxoisoaporphine–tetrahydroisoquinoline: novel multi-target inhibitors of inflammation and amyloid-β aggregation in Alzheimer’s disease - Yusi Chen; Chunlin Su; Li Wang; Jingfang Qin; Shenqi Wei; Huang Tang (Molecular Diversity, 2019)

Computational Study of HCV p7 Channel: Insight into a New Strategy for HCV Inhibitor Design - Beili Ying; Shichao Pang; Junchen Yang; Yang Zhong; Jingfang Wang (Interdisciplinary Sciences: Computational Life Sciences, 2019)

OsNDUFA9 encoding a mitochondrial complex I subunit is essential for embryo development and starch synthesis in rice - Tingting Hu; Yunlu Tian; Jianping Zhu; Yunlong Wang; Ruonan Jing; Jie Lei; Yinglun Sun; Yanfang Yu; Jingfang Li; Xiaoli Chen; Xiaopin Zhu; Yuanyuan Hao; et al. (Plant Cell Reports, 2018)

Complete genome sequence of a novel lytic bacteriophage isolated from Ralstonia solanacearum - Jingfang Su; Hongwei Sun; Junjie Liu; Zhaokui Guo; Guoquan Fan; Gang Gu; Guanghua Wang (Archives of Virology, 2017)

Proper balance of omega-3 and omega-6 fatty acid supplements with topical cyclosporine attenuated contact lens-related dry eye syndrome - Ling Wang; Xi Chen; Jingfang Hao; Lu Yang (Inflammopharmacology, 2016)

The germin-like protein OsGLP2-1 enhances resistance to fungal blast and bacterial blight in rice - Qing Liu; Jianyuan Yang; Shijuan Yan; Shaohong Zhang; Junliang Zhao; Wenjuan Wang; Tifeng Yang; Xiaofei Wang; Xingxue Mao; Jingfang Dong; Xiaoyuan Zhu; Bin Liu (Plant Molecular Biology, 2016)

MicroRNA-135b regulates metastasis suppressor 1 expression and promotes migration and invasion in colorectal cancer - Weiyun Wu; Zhuang Wang; Pengchun Yang; Jingfang Yang; Jian Liang; Yuanhong Chen; Hao Wang; Guoli Wei; Shicai Ye; Yu Zhou (Molecular and Cellular Biochemistry, 2014)

Construction and characterization of the interdomain chimeras using Cry11Aa and Cry11Ba from Bacillus thuringiensis and identification of a possible novel toxic chimera - Yunjun Sun; Qiang Zhao; Dasheng Zheng; Xuezhi Ding; Jingfang Wang; Quanfang Hu; Zhiming Yuan; Hyun-Woo Park; Liqiu Xia (Biotechnology Letters, 2014)

A bFGF Antagonist Peptide with Anti-angiogenesis Properties in Non-small Cell Lung Cancer Cells - Ruixue Wang; Wu Luo; Xiangfeng Zeng; Jingfang Di; Yonglin Yu; Chuan Wang; Wenhui Wang; Xilei Chen; Dan He; Tao Li; Xiaoping Wu (International Journal of Peptide Research and Therapeutics, 2013)

Steroidal saponins from the rhizomes of Polygonatum odoratum - Dongmei Wang; Dengwu Li; Wei Zhu; Jingfang Zhang; Pai Peng (Natural Product Research, 2009)